Descriptive study of the kinds of questions asked by novice teacher on mathematics learning process - Labiba Zahra; Tri Atmojo Kusmayadi; Budi Usodo (International Journal of Science and Applied Science: Conference Series, 2017)
This study described the kinds of a question asked by novice teacher on mathematics learning process of senior high school. The data were collected by passive participation observation and a semi-structured interview. The validity of data was obtained through the triangulation of method, triangulation of time and member check. The data analysis technique used in this study is descriptive analysis. The result of this study showed that at the preliminary activity, the question asked by the novice teacher based on objective only compliance question. At the main activity, the novice teacher asked compliance question, prompting question, probing question and sometimes rhetorical question. The kind of questions based on the cognitive dimension of Revised Bloom’s Taxonomy that was asked by novice teacher only remembering question. At the main activity, the novice teacher asked the question of remember, understand, apply, analyse and evaluate. At the closing activity, the teacher does not ask the question based on objective and Revised Bloom’s Taxonomy.